The Progress in the Field Auxiliary Donors and their Application in Novel Organic Second-Order Nonlinear Optical Chromophores - Gao, Wu; Liu, Jialei; Kityk, Iwan V. (Mini-Reviews in Organic Chemistry, 2019)
Conversion efficiency between electrical and optical signals is very important for the development of modern information technologies. Due to their advantages in half-wave voltage, bandwidth, cost and integration, as well as organic electro-optic (EO) parameters, these materials are widely studied and used in microwave photonic devices. Second order nonlinear optical (NLO) chromophores, as the core of organic EO materials have an increasing interest in this branch. Auxiliary donors present a new direction for the design and improvement of organic NLO chromophores. In this short review, the advantages, theoretical calculations and experimental results of auxiliary donors are reviewed and discussed in detail.
Keywords: NLO